2017
DOI: 10.1159/000479481
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Future Trends to Optimize the Care of Chronic Kidney Disease in African Americans

Abstract: Background: African Americans (AAs) suffer the widest gaps in chronic kidney disease (CKD) outcomes compared to Caucasian Americans (CAs) and this is because of the disparities that exist in both health and healthcare. In fact, the prevalence of CKD is 3.5 times higher in AAs compared to CAs. The disparities exist at all stages of CKD. Importantly, AAs are 10 times more likely to develop hypertension-related kidney failure and 3 times more likely to progress to kidney failure compared to CAs. Summary: Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
0
15
0
2
Order By: Relevance
“…Studies were conducted in the US, Canada, UK, and Norway and most were prospective or retrospective cohort studies. Overall, most (n = 24) studies reported higher risk of CKD progression in African-American/Afro-Caribbean [13][14][15][16][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, some (n = 12) studies found no significant ethnic differences in risk of CKD progression, which may be partly due to smaller study sample size, duration of follow up, and/or adjustment for confounders and mediators [9,[38][39][40][41][42][43][44][45][46][47][48].…”
Section: Ethnic Differences In Ckd Progression African-americans and mentioning
confidence: 98%
See 1 more Smart Citation
“…Studies were conducted in the US, Canada, UK, and Norway and most were prospective or retrospective cohort studies. Overall, most (n = 24) studies reported higher risk of CKD progression in African-American/Afro-Caribbean [13][14][15][16][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, some (n = 12) studies found no significant ethnic differences in risk of CKD progression, which may be partly due to smaller study sample size, duration of follow up, and/or adjustment for confounders and mediators [9,[38][39][40][41][42][43][44][45][46][47][48].…”
Section: Ethnic Differences In Ckd Progression African-americans and mentioning
confidence: 98%
“…Our updated searches identified 5 relevant studies published between July 2017 and February 2020, resulting in a total of 55 studies included in the review. These 55 studies included 1 systematic review [9] and 8 literature reviews on CKD progression [12][13][14][15][16][17][18][19]. Together these reviews included 19 of the individual studies identified in our searches.…”
Section: Search Strategy Study Selection and Data Extractionmentioning
confidence: 99%
“…For example, it is possible that African-Americans are more likely to receive fragmented care, and we may underestimate care delivered. 40,41 We also do not have data in our CKD registry about other delivery outcomes such as referral for dialysis modality education or goals of care discussions. Finally, our regression analyses are limited to age, sex, and relevant comorbidities and do not include adjustment based on other important attributes, such as socioeconomic status, due to limitations of the registry.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…other biologic pathways (6)(7)(8)(9)(10). Among the many biologic mechanisms underlying DN, inflammation in the kidney by mononuclear phagocytic lineage cells (9)(10)(11) and the impact of growth factors and proinflammatory cytokines, such as IL-1, IL-6, IL-18, and TNF-a, and other chemokines may have direct or indirect contributions to the pathogenesis of DN (12,13).…”
mentioning
confidence: 99%